The Role of Employee Engagement on Organizational Commitment - Rahayu, Puspita Puji (SEIKO : Journal of Management & Business, 2023)
This study aims to investigate the effects of organizational learning, work environment, and employee participation on organizational commitment to DNS Semarang technology. This study, which falls under the category of explanatory research, employs quantitative methods. With a sample size of 332 respondents, this study was done in a DNS technology company with a total of 2,671 employees. The data is processed using Lisrel's Findings from the research indicate that organizational commitment is positively and significantly impacted by employee involvement in the business. Employee engagement is significantly and favorably impacted by the workplace. Organizational commitment is positively and significantly impacted by organizational learning. The results of this study show that companies that employ employees in a variety of roles provide them chances to reach their full potential and feel more a part of the company. To strengthen organizational commitment, it is necessary to keep improving the on-site and off-site working conditions. Similar to this, organizational learning must be applied to employees continuously to improve their knowledge, skills, and competences. Employees need to feel there are self-development programs that can boost organizational commitment, thus leaders must promote organizational learning among their workforce. Keywords: Organizational Commitment, Employee Engagement, Organizational Learning